Discussion on the evaluation of the therapeutic efficacy of uterine artery blood flow parameters and serum PLGF and sFlt-1 in patients with recurrent spontaneous abortion - Xiaolu Lian; Yanyu Zhong; Ying Zhou; Fei Xia; Ru Sun (BMC, 2024)
Abstract Objective To investigate the effects of different drug treatments on uterine artery blood flow parameters, serum placental growth factor (PLGF), soluble fms-like tyrosine kinase-1 (sFlt-1), and sFlt-1/PLGF in patients with recurrent spontaneous abortion and to explore the predictive value of uterine artery blood flow parameters, serum PLGF, sFlt-1, and sFlt-1/PLGF for pregnancy outcomes. Methods This retrospective cohort study included 173 patients who experienced recurrent spontaneous abortion and 100 control patients. Patients with recurrent spontaneous abortion were divided into an aspirin group (75 patients), aspirin combined with low molecular weight heparin (LMWH) group (68 patients), and non-drug group (30 patients) based on different drug treatments. Uterine artery blood flow parameters at gestational weeks 30-31+6 were monitored for the four groups, and serum samples were collected at gestational weeks 30-31+6 to measure the levels of serum PLGF and sFlt-1 and calculate the sFlt-1/PLGF ratio. Results 1. Uterine artery blood flow parameters at gestational weeks 30-31+6 were significantly greater in the non-drug group than in the aspirin group, combined drug group, and control group (p<0.05). 2. Serum PLGF levels and the sFlt-1/PLGF ratio at gestational weeks 30-31+6 were significantly lower in the non-drug group than in the aspirin group, combined drug group, and control group, while serum sFlt-1 levels were significantly greater in the non-drug group than in the aspirin group, combined drug group, and control group (p<0.05). 3. Serum PLGF, sFlt-1, and sFlt-1/PLGF had lower diagnostic efficiency for predicting hypertensive disorders during pregnancy than the combined diagnostic efficiency of serum PLGF, sFlt-1, and sFlt-1/PLGF with uterine artery blood flow parameters at gestational weeks 30-31+6. Conclusion Aspirin and aspirin combined with LMWH can upregulate serum PLGF and decrease serum sFlt-1 levels in patients with recurrent spontaneous abortion, reduce the miscarriage rate, and significantly improve pregnancy outcomes. The combination of serum PLGF, sFlt-1, sFlt-1/PLGF, and uterine artery blood flow parameters can effectively predict hypertensive disorders during pregnancy.